Iowa Birdline update, November 21-28, 1988 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1988)
Notes for the Iowa Birdline update for November 21-28, 1988. Highlights of the update include a variety of water bird sightings due to the fact the lakes and ponds remain unfrozen. Other interesting observations include a Rock Wren, a Black-legged Kittiwake, a Trumpeter Swan, a Tundra Swan, and several species of Owls. Epson - sheet feed/flatbed